2015
DOI: 10.1021/es506007q
|View full text |Cite
|
Sign up to set email alerts
|

Daphnid Life Cycle Responses to the Insecticide Chlorantraniliprole and Its Transformation Products

Abstract: Chlorantraniliprole (CAP) is a newly developed, widely applied insecticide. In the aquatic environment, several transformation products are formed under natural conditions, one by dehydration and others by photoinduced degradation. Data on aquatic ecotoxicity of CAP can mainly be found in registration and regulatory evaluation reports. Moreover, the toxicity of its transformation products and especially effects upon chronic exposure remain completely unknown. Hence, our aim was to investigate the acute and chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 30 publications
(59 reference statements)
1
12
1
Order By: Relevance
“…Estimated LC50 values of CAP for S. vittatum (48‐h LC50 of 15.4 µg/L) were within the range reported for the most sensitive species: the cladoceran Daphnia magna (LC50 of 9.4 µg/L) , the ephemeropteran Centroptilum triangulifer (LC50 of 11.6 µg/L) , and the trichopteran Chimarra atterima (LC50 of 11.7 µg/L) . A higher tolerance to CAP has been reported for the dipteran Chironomus riparius (LC50 of 77.5 µg/L) .…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Estimated LC50 values of CAP for S. vittatum (48‐h LC50 of 15.4 µg/L) were within the range reported for the most sensitive species: the cladoceran Daphnia magna (LC50 of 9.4 µg/L) , the ephemeropteran Centroptilum triangulifer (LC50 of 11.6 µg/L) , and the trichopteran Chimarra atterima (LC50 of 11.7 µg/L) . A higher tolerance to CAP has been reported for the dipteran Chironomus riparius (LC50 of 77.5 µg/L) .…”
Section: Discussionsupporting
confidence: 68%
“…Chlorantraniliprole (CAP), the first anthranilic diamide commercially available, targets the ryanodine receptor channels of insects, disrupting calcium homeostasis in muscle cells and neurons, leading to abnormal muscular contractions that result in paralysis and death of target pests . However, CAP has been shown to be toxic to nontarget aquatic invertebrate species . Furthermore, CAP has been reported to be a persistent compound , and measured concentrations in surface waters ranging from 0.1 μg/L to 9.7 μg/L confirm its potential ecological effects on freshwater ecosystems, exceeding the US Environmental Protection Agency (USEPA) benchmarks for acute/chronic (4.9/4.5 μg/L CAP) toxicity to freshwater invertebrates .…”
Section: Introductionmentioning
confidence: 99%
“…Even with the reported toxicity of chlorantraniliprole in different doses to non-target organisms belonging to various groups, such as Daphnia magna (Crustacea) (LAVTIZAR et al, 2015) and to nymphs of Amphiareus constrictus (Stal) and Blaptostethus pallescens (Poppius) (Heteroptera: Anthocoridae) (GONTIJO et al, 2015), in general, this study found no significant influence of this product on the development of T. podisi. Accordingly, the product shows characteristics that allow us to consider it to be selective (LAHM et al, 2009;SPARKS et al, 2015).…”
Section: Discussioncontrasting
confidence: 93%
“…This effect has been confirmed in other studies. 28,32,33) Difenoconazole is a triazole fungicide that controls a wide spectrum of foliar, soil-borne, and seed diseases. 34) It is used as a curative and preventative fungicide applied as a seed treatment and foliage spray for various crops, including fruits and vegetables.…”
Section: Residual Pesticide Levels In Hot Pepper Powdermentioning
confidence: 99%